Reproductive ecology of interior least tern and piping plover in relation to Platte River hydrology and sandbar dynamics - Alexander, Jason S. (Ecol Evol, 2018)
In a recent study, Farnsworth et al. (2017) used distributions of nest initiation dates drawn mostly from human‐created, off‐channel habitats and a model of emergent sandbar habitat to evaluate the hypothesis that least terns (Sternula antillarum) and piping plovers (Charadrius melodus) are physiologically adapted to initiate nests concurrent with the cessation of spring river flow rises on two sections of the Platte River, Nebraska. The study by Farnsworth et al. (2017) has several shortcomings which bring into question the authors’ principal assertion that interior least tern and piping plovers are not adapted to occupying and nesting on river sandbars on the Platte River system. We identify these shortcomings and provide information, which, we suggest, would change their conclusions if incorporated. [Image: see text] Linked Article: https://doi.org/10.1002/ece3.4097